Analysis of the Correlation between Nutritional Status and Quality of Life of Patients with Gynaecological Ovarian Cancer during Postoperative Chemotherapy. (22nd June 2022) - Shi, Xiaoming; Lv, Yuchun; Wang, Peiqi; Yang, Xin; You, Shengjun
Abstract : Ovarian cancer mortality is on the rise in China. Surgery followed by adjuvant chemotherapy is the most extensively used treatment for tumour recovery. An excellent nutritional condition prior and throughout treatment serves to improve the quality of life and, as a result, the treatment result. The goal of this research was how diet affected the functioning standard of those living in carcinoma who were receiving postoperative treatment. BMI was utilised to evaluate nutrition, accompanied by albuminemia, prealbuminemia, and serum C-reactive protein, that is used to evaluate excessive catabolism. The QLQ-C30 questionnaire assessed standard of living. The performance status of the patient is decided with the help of the WHO performance scale for cancer patients. The study identified the statistically significant relationship between the performance status and hypercatabolism in the global health (quality of life) of the patient. While body mass index is often considered as a standard for assessment of nutritional status, it has affected only the cognitive function of the patient. In this study, we have concluded that in addition to direct measurement of the BMI, other clinical parameters such as serum CRP should be considered to get a better outcome of chemotherapy.